The Challenges of International Education: Developing a Public Relations Unit for the Asian Region - Fitch, K.; Surma, A. (Journal of University Teaching and Learning Practice, 2006)
Murdoch University’s public relations program attracts asignificant number of international students. Up to 60% ofstudents in some units come from Singapore and Malaysia.While many spend at least one year in Australia as part of thethree year degree, students in both countries may complete theentire degree offshore from 2007.The authors rewrote a second year public relations unit with theaim of making it more relevant for local and internationalstudents. This posed particular challenges in terms ofpedagogical and conceptual approaches. For instance, thereare cultural and linguistic issues which influence the waysstudents learn, and which have particular implications for a unitwhich expressly aims to consolidate students’ professionalwriting skills. There are also implications for public relationstheory, which tends to be dominated by Western concepts andmodels, and public relations practice, which varies in differentcountries.This paper offers a reflection on the issues we addressed in theredevelopment of the unit, as well as some suggestions forfuture teaching and learning practices.